Pengaruh penggunaan media kartu gambar berbasis augmented reality (ar) terhadap keterampilan menulis puisi peserta didik kelas iv sekolah dasar - Nida Nur Afifah; Rukayah Rukayah; Septi Yulisetiani (Didaktika Dwija Indria, 2025)
Abstract.This research purpose is to identify the effect of using augmented reality (AR)-based picture card media on the poetry writing skills of fourth grade elementary school students. Quantitative research method Quasi Experiment Nonequivalent Pretest-Posttest Control Group design. The research population was public elementary schools in Laweyan sub-district, the sample was determined by Cluster Random Sampling. The data collection technique was a poetry writing skill test. Instrument validity test with Expert Judgment and Alpha Cronbach reliability test. Research prerequisite tests: Shapiro Wilk normality test, Levene homogeneity test, and T-test balance test. Hypothesis testing with Independent Sample T-test. The average post-test score showed that the control group was 73.04 and the experimental group was 80.77. The results of the percentage of achievement of the experimental group's poetry writing skills indicators were higher than the control group in the aspects of theme, rhyme, majas, diction, and imagery. The results of the hypothesis test value (sig.) 0.002 <0.05 (H0 rejected), there is a significant effect of using augmented reality (AR) based picture card media on poetry writing skills. The effect occurs due to the use of media in learning to write poetry. This media can visualize 3D interestingly so that it helps students understand the material more concretely, provides new experiences, stimulates creativity, vocabulary, imagination, interaction, and learning motivation. The implication of the research is that it is an important input for teachers in considering the use of creative and innovative media so that the provision of stimulation has an effect on learning outcomes.  Abstract.This research purpose is to identify the effect of using augmented reality (AR)-based picture card media on the poetry writing skills of fourth grade elementary school students. Quantitative research method Quasi Experiment Nonequivalent Pretest-Posttest Control Group design. The research population was public elementary schools in Laweyan sub-district, the sample was determined by Cluster Random Sampling. The data collection technique was a poetry writing skill test. Instrument validity test with Expert Judgment and Alpha Cronbach reliability test. Research prerequisite tests: Shapiro Wilk normality test, Levene homogeneity test, and T-test balance test. Hypothesis testing with Independent Sample T-test. The average post-test score showed that the control group was 73.04 and the experimental group was 80.77. The results of the percentage of achievement of the experimental group's poetry writing skills indicators were higher than the control group in the aspects of theme, rhyme, majas, diction, and imagery. The results of the hypothesis test value (sig.) 0.002 <0.05 (H0 rejected), there is a significant effect of using augmented reality (AR) based picture card media on poetry writing skills. The effect occurs due to the use of media in learning to write poetry. This media can visualize 3D interestingly so that it helps students understand the material more concretely, provides new experiences, stimulates creativity, vocabulary, imagination, interaction, and learning motivation. The implication of the research is that it is an important input for teachers in considering the use of creative and innovative media so that the provision of stimulation has an effect on learning outcomes.Kata kunci: picture card media, augmented reality, poetry writing skills, elementary school